Public or private job matching for immigrant workers an outline of a Swedish social experiment - Kenneth Carling; Helge Bennmarker; Anders Forslund (Institute for Labour Market Policy Evaluation (IFAU), 2001)
Evaluations of labour market programs and other related measures typically make use of observational data. This paper presents an outline for producing experimental data in the interest of testing a proposed measure targeted to un-employed immigrant workers. The idea is to offer them placement services provided by a private recruitment company as well as by public employment offices. The assignment of unemployed immigrants to the two providers will be random and the operating conditions kept as similar as possible.
Keywords: J29; J70; 330; Unemployed immigrants; job matching; experiment